Art and the war at sea, 1914-1945 - Riding, Christine (Lund Humphries in association with the National Maritime Museum, 2015)
Drawing on the rich archives held at the National Maritime Museum, London, this beautifully illustrated book is the first study to focus on war art of the first half of the 20th century from a distinctly naval and maritime perspective.